Assessment of self-rated health 5 years after Roux-en-Y gastric bypass for severe obesity. Issue 6 (30th September 2019) - Sandvik, J; Hole, T; Klöckner, C A; Kulseng, B E; Wibe, A
Abstract: Background: Patients' perceptions of health change after bariatric surgery are complex. The aim of this study was to explore whether self-rated health (SRH), a widely used tool in public health research, might be relevant as an outcome measure after Roux-en-Y gastric bypass (RYGB) for severe obesity. Methods: This was a single-centre retrospective study of a local quality registry. SRH score was registered at baseline and 5 years after RYGB. SRH, one of the 36 items in the quality-of-life Short Form 36 (SF-36®) questionnaire, is the answer to this single question: 'In general, would you say your health is excellent (1), very good (2), good (3), fair (4) or poor (5)?' Change in SRH was analysed in relation to change in weight, co-morbidities and quality of life after 5 years. Results: Of a total of 359 patients who underwent RYGB between September 2006 and February 2011, 233 (64·9 per cent) reported on SRH before and 5 years after surgery. Of these, 180 (77·3 per cent) were women, and the mean(s.d.) age was 40(9) years. Some 154 patients (66·1 per cent) reported an improvement in SRH, 60 (25·8 per cent) had no change, and SRH decreased in 19 patients (8·2 per cent). SRH in improvers was related to better scores in all SF-36® domains, whereas SRH in non-improvers was related to unchanged or worsened scores in all SF-36® domains except physical function. Conclusion: Two-thirds of patients reported improved SRH 5 years after RYGB for severe obesity. In view of its simplicity, SRH may be an easy-to-use outcome measure in bariatric surgery. Graphical Abstract: A single question on self-rated health (SRH) could provide an easy-to-use outcome measure in bariatric surgery. Two-thirds of patients who had Roux-en-Y gastric bypass for severe obesity reported improved SRH after 5 years. Self-rated health - One question to replace a questionnaire?